The Rokat Tase' Tradition in Enhancing Social Solidarity The Community in Tamberu Sokobanah Sampang - Alifcahyono, Raihan; Faraniena Yunaeni Risdiana (Institut Agama Islam Negeri Madura, 2026)
This study focuses on the implementation process of the Rokat Tase' tradition in Tamberu Sokobanah Sampang Village and the Rokat Tase' tradition in enhancing social solidarity among the community in Tamberu Sokobanah Sampang Village according to Emile Dhurkheim. This study uses a descriptive qualitative research approach with three data collection procedures, namely: semi-structured interviews, non-participant observation, and documentation. To analyze the data, the researcher used several steps, namely data analysis such as data reduction, data reduction, data presentation, and drawing conclusions. Meanwhile, data validity was checked through the researcher's diligence and triangulation of data sources. From this study, it can be concluded that the implementation of the Rokat Tase' tradition in Tamberu Sokobanah Sampang Village consists of three main stages, namely The preparation stage is usually carried out by the coastal community long before the event begins, especially the preparations for hiring the ludruk art troupe. The implementation stage is carried out in the month of Muharram or Suro. The ritual generally lasts for 2-3 days. The closing stage includes an art performance as an expression of joy for the event, then the ritual ends with a prayer together. The Rokat Tase' tradition in Tamberu Sokobanah Sampang Village is quite effective in enhancing social solidarity among the community.